The European Parliament's Role in EU Treaty-Making. Issue 6 (December 2016) - Ott, Andrea
The European Parliament's role in EU external relations and treaty-making has increased over the years through constitutional practice and Treaty amendments. Finally, with the Treaty of Lisbon, the European Parliament's constitutional rights in treaty-making establish – in the words of the European Court of Justice (CJEU) – 'symmetry between legislation-making and treaty-making in compliance with institutional balance provided for by the Treaties'. In a comparative overview, the European Parliament has ascertained more extensive powers over treaty-making compared to the majority of national parliaments which are only involved in politically important international treaties. This contribution addresses the consequences of this symmetry or parallelism and asks whether it leads to structural symmetry or even procedural symmetry which synchronizes the acts of legislating and treaty-making with each other. This contribution analyses the role of the European Parliament in the different phases of international treaty-making against the backdrop of this constitutional practice. This constitutional practice is shaped by intergovernmental agreements, bilateral arrangements and European Parliament resolutions and is influenced by the mounting case law of the CJEU. It also assesses the European Parliament's role in concluding international administrative agreements concluded by the Commission and Europol and how far the constitutional practice is in line with EU primary law.